Pengembangan Bahan Ajar Gamifikasi pada Materi Himpunan - Wirawan, Yosi Marenda; Putra, Rizki Wahyu Yunian (Universitas Islam Negeri Raden Intan Lampung, 2018)
The purpose of this study is to know whether the development of teaching materials gamification for seventh-grade students is feasible and interesting for use in junior high school. The subjects of the experiment were seventh-grade students at SMP Bandar Lampung. This research method is Research and Development (R&D), which a using Borg and Gall development model. The results of the assessment are: the expert assessment of the material giving a scored with an average percentage of 76% is categorized as highly feasible, the media or design experts scored with an average percentage of 71% categorized as feasible and the linguist gave a score with an average percentage of 69% categorized as feasible. In small group trials, an average of 3,6 was obtained with very attractive and feasible categories. In the field trial, it was found that the average of 3,4 was obtained with very attractive and feasible categories and the teacher's response to the materials gamifikasi, it was found that the average of 3,3 was obtained with very attractive and feasible categorized. So it can be concluded that the gamification teaching materials on the are categorized very attractive and feasible for use in mathematics learning in junior high school.